Persembahan Yang Layak Di Hadapan Tuhan Ditinjau Dari Kejadian 4:1-16 - Wasti Wasti; Yublina kasse (Universitas Katolik Widya Karya Malang, 2023)
Humans are basically spiritual beings. Because, a person can mentally react to something. Humans have always tried to relate to the divine. So the relationship with the god is in the form of worship. The concept of worship in both the Old and New Testaments is the same concept. The Hebrew word for century and the Greek for the beginning of latreia denote the occupation of slaves. And to perform